PENGARUH WORK LIFE BALANCE DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PADA IKATAN ALUMNI UNIVERSITAS ADVENT INDONESIA - Nissa Aulia Cantica Ujudeda; Grace Orlyn Sitompul (POLITEKNIK LP3I JAKARTA, 2024)
In an increasingly competitive work environment, perceived employee job satisfaction becomes a crucial element influencing productivity. Therefore, it is imperative for companies to prioritize employee satisfaction in order to remain relevant in a challenging business environment. This study evaluates factors influencing the level of job satisfaction among alumni of Adventist University of Indonesia using multiple linear regression analysis method. Independent variables such as work-life balance and leadership style are evaluated against job satisfaction. The aim is to analyze the impact of work-life balance and leadership style on alumni job satisfaction. A total of 90 alumni were selected as research samples using the Slovin formula. Data analysis involved multiple linear regression, including simultaneous (F- test) and partial (t-test) tests, conducted using SPSS software version 23.0. The research findings conclude that both work life balance and leadership style significantly influence job satisfaction among employees in the Adventist University of Indonesia alumni environment. Key words: Employee Job Satisfaction, Work Life Balance, Leadership Style